2000
DOI: 10.1029/1999jd901124
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime precipitation behavior in the western Canadian Arctic region

Abstract: Abstract. To investigate the precipitation formation process in the two major types of weather systems ("Pacific origin" and "storm track" types) in the western Canadian Arctic region, an X-band vertical pointing Doppler radar, microwave radiometer were installed at Inuvik, Northwest Territories, Canada, during the midwinter of 1995/1996. Precise precipitation observations specially for ice crystals with replicator, microscope, and closeup photos were also conducted at the same place. Precipitation formation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…(with . These values are characteristic of orographic clouds (Asuma et al, 2000). The profile at 8:00 UTC reveals saturation in only the first few meters above the surface.…”
Section: Mmwr Measurementsmentioning
confidence: 96%
“…(with . These values are characteristic of orographic clouds (Asuma et al, 2000). The profile at 8:00 UTC reveals saturation in only the first few meters above the surface.…”
Section: Mmwr Measurementsmentioning
confidence: 96%
“…Pacificorigin disturbances and subsequently lee cyclogenesis could occur over the Mackenzie Mountains and affect weather in Norman Wells, just as they do in the southern MRb (e.g., Lackmann and Gyakum, 1996) or in the northern MRB (Asuma et al, 1998(Asuma et al, , 2000. However, the amount of precipitation would be affected by the presence or absence of lowlevel moisture (e.g., Asuma et al, 1998Asuma et al, , 2000Stewart et al, 2004). Figure 1, which shows the November synoptic climatology, also illustrates two opposing processes that affect winter roads.…”
Section: Background Climate Of the Northwest Territoriesmentioning
confidence: 99%
“…In the Arctic (northern coast of Alaska), Mossop et al [38] and Jayaweera and Ohtake [39] investigated the microphysical characteristics of arctic stratus clouds, observing no riming process in these clouds. Instead, Asuma et al [40] observed both densely rimed dendrites and graupels in the western Canadian Arctic together with crystals grown by diffusion (plates, columns, bullet rosettes). These two different growth [41] collected snow and ice crystals in the air, on the ground and on sea-ice in Alaska to study the deposition of mercury, predominantly present in the atmosphere as a gaseous element.…”
Section: Physical and Chemical Processesmentioning
confidence: 99%